Alginate-derived oligosaccharides obtained from enzymatic hydrolysis of Laminaria improve temperature adaptability and increase bioactive compound yield in Phaeodactylum tricornutum - Xingkai Che; Dingning Fan; Ruirui Ding; Litao Zhang; Benwei Zhu; Yongfu Li (Bioresource Technology, 2026)

Long-term fertilization enhances Bacilli cell size by increasing soil resource availability and shifting its metabolic strategies - Nan Rong; Youzhi Feng; Ruirui Chen; Yuanyuan Bao; Shiying He; Shudong Ding; Xiaoyuan Yan (Agriculture, Ecosystems & Environment, 2026)

Robust photothermal regulation in large-area smart windows enabled by bimetallic NiCo hydroxide with layered structure - Yi Gao; Xiaoting Li; Qiaodeng Ding; Pengyang Lei; Xinyi Wang; Chengyu Hu; Ruirui Ren; Jinhui Wang; Guofa Cai (Chemical Engineering Journal, 2026)

Drosophila Tet mediates the host IMD antibacterial immune defense in a catalytic activity-independent manner - Chuchu Zhang; Muhammad Abdul Rehman Saeed; Yiheng Jin; Erwen Ding; Yajie Su; Sheng Hu; Ruirui Tan; Shanming Ji (Insect Biochemistry and Molecular Biology, 2026)

Drosophila PcG-repressive deubiquitinase complex mediates antibacterial immune defense via transcriptional regulation of Calcineurin A1 - Umar Ali; Ruirui Tan; Sheng Hu; Sen Ding; Badar Raza; Qingshuang Cai; Shanming Ji (Insect Biochemistry and Molecular Biology, 2026)

High-molecular weight hyaluronic acid protects against colitis by remodeling microbiota and restoring barrier function - Xinwei Gao; Hao Huang; Litao Hu; Weiquan Ding; Zhiliang Hou; Ruirui Xu; Guochen Du; Zhen Kang (Carbohydrate Polymers, 2026)

Precision detection and geolocation of missed pre-tassels in hybrid maize seed production using UAV-based deep learning - Chenchen Ding; Ruirui Zhang; Jiangtao Qi; Yuxin Xie; Tongchuan Yi; Longlong Li; Mingqi Wu; Weirong Zhang; Zhiyuan Bao (European Journal of Agronomy, 2026)

Scalable ergothioneine production via integrating chemical methylation and rhodanese-catalyzed CS bond formation - Jie Lu; Xiaoyuan Sun; Hanzhi Weng; Weiquan Ding; Fengling Yang; Guochen Du; Ruirui Xu; Zhen Kang (Chemical Engineering Journal, 2026)

Atrazine-induced hippocampal neurotoxicity: Involvement of Drp1-mediated mitochondrial fission - Jingran Yang; Ling Qi; Cheng Zhang; Ruirui Ding; Haoran Bi; Peng Li; Zhipeng Qi; Qiao Niu; Weiyi Song; Jianan Li (Chemico-Biological Interactions, 2025)

Establishment of reference intervals for serum immunoglobulin G N-glycosylation features in healthy Chinese adults: a nationwide survey in the framework of predictive, preventive, and personalized medicine - Changyu Liu; Yinghao Wang; Xingang Li; Xiaojia Xu; Ruirui Xu; Cuihong Tian; Zhixian Chen; Xinxia Lu; Yuejin Li; Meng Wang; Zhaoyang Tang; Xueyu Chen; et al. (EPMA Journal, 2025)

Exploring the mechanisms of hippocampal neurotoxicity induced by cypermethrin: Insights from integrated miRNA-seq and mRNA-seq analysis - Jingran Yang; Ruirui Ding; Ling Qi; Haoran Bi; Jianan Li (Environmental Toxicology and Pharmacology, 2025)

Path curvature incorporated reinforcement learning method for accurate path tracking of agricultural vehicles - Linhuan Zhang; Ruirui Zhang; Danzhu Zhang; Tongchuan Yi; Chenchen Ding; Liping Chen (Computers and Electronics in Agriculture, 2025)

Research progress on the synergistic effect and its mechanisms of antidepressants and antibiotics against resistant pathogens - Lihong Ding; Xia Chen; Yanli Lv; Qianyu Peng; Ruirui Wang; Bo Yang; Lianhua Wei (Archives of Microbiology, 2025)

Alginate-derived oligosaccharides (AOS) enhance the biomass of Phaeodactylum tricornutum and fucoxanthin yield - Xingkai Che; Dingning Fan; Ruirui Ding; Haixing Wu; Yongfu Li (Journal of Applied Phycology, 2025)

YOLO-detassel: Efficient object detection for Omitted Pre-Tassel in detasseling operation for maize seed production - Jiaxuan Yang; Ruirui Zhang; Chenchen Ding; Liping Chen; Yuxin Xie; Hong Ou (Computers and Electronics in Agriculture, 2025)

Transcriptome-Wide Analysis Revealed the Influential Role of PbrMTP (Metal Tolerance Protein) in the Growth and Fruit Development of Chinese White Pear - Ruirui Xu; Ahmad Ali; Ying Li; Xiao Zhang; Rahat Sharif; Xinxin Feng; Baopeng Ding (Journal of Plant Growth Regulation, 2025)

The effect of stem contact fermentation on the quality of Cabernet Sauvignon and Merlot wines from Yantai, China - Ruirui Li; Dongyue Yang; Zhiyu Li; Xiaohong Tang; Ke Zhong; Yan Ding; Xiaomei Han; Xueqiang Guan; Yuxia Sun (Food Bioscience, 2025)

Trifluoperazine effect on human sperm: The accumulation of reactive oxygen species and the decrease in the mitochondrial membrane potential - Houpeng Wang; Cheng Cheng; Jing Ding; Ruirui Qian; Tao Luo; Liping Zheng; Ying Chen (Reproductive Toxicology, 2024)

Grape Seed Proanthocyanidins Protect Pancreatic β Cells Against Ferroptosis via the Nrf2 Pathway in Type 2 Diabetes - Haiyan Li; Haowei Zhang; Tongling Wang; Liyuan Zhang; Hao Wang; Heng Lu; Ruirui Yang; Yusong Ding (Biological Trace Element Research, 2024)
Pancreatic β cell damage is the primary contributor to type 2 diabetes mellitus (T2DM); however, the underlying mechanism remains nebulous. This study explored the role of ferroptosis in pancreatic β cell damage and the protective effects of grape seed proanthocyanidin extract (GSPE). In T2DM model rats, the blood glucose, water intake, urine volume, HbA1c, and homeostasis model assessment-insulin resistance were significantly increased, while the body weight and the insulin level were significantly decreased, indicating the successful establishment of the T2DM model. MIN6 mouse insulinoma β cells were cultured in high glucose and sodium palmitate conditions to obtain a glycolipid damage model, which was administered with GSPE, ferrostatin-1 (Fer-1), or nuclear factor erythroid 2-related factor 2 (Nrf2) small interfering (si) RNA. GSPE and Fer-1 treatment significantly improved pancreatic β-cell dysfunction and protected against cell death. Both treatments increased the superoxide dismutase and glutathione activity, reduced the malondialdehyde and reactive oxygen species levels, and improved iron metabolism. Furthermore, the treatments reversed the expression of ferroptosis markers cysteine/glutamate transporter (XCT) and glutathione peroxidase 4 (GPX4) caused by glycolipid toxicity. GSPE treatments activated the expression of Nrf2 and related proteins. These effects were reversed when co-transfected with si-Nrf2. GSPE inhibits ferroptosis by activating the Nrf2 signaling pathway, thus reducing β-cell damage and dysfunction in T2DM. Therefore, GSPE is a potential treatment strategy against T2DM. Graphical Abstract

Potassium Permanganate/Persulfate Combined Oxidation Remediation of Petroleum Contaminated Soil - Xiuxia Zhang; Kangning Dong; Boyu Hao; Mingshan Ding; Shuai Zuo; Ruirui Wang; Ruyue Li (Water, Air, & Soil Pollution, 2024)

Toward a remote sensing method based on commercial LiDAR sensors for the measurement of spray drift and potential drift reduction - Longlong Li; Ruirui Zhang; Liping Chen; Andrew J. Hewitt; Xiongkui He; Chenchen Ding; Qing Tang; Boqin Liu (Science of The Total Environment, 2024)

Nitrogen improves plant cooling capacity under increased environmental temperature - Ruirui Wang; Jixing Zeng; Kehao Chen; Qihui Ding; Qirong Shen; Min Wang; Shiwei Guo (Plant and Soil, 2022)

The severe toxicity of CuO nanoparticles to the photosynthesis of the prokaryotic algae Arthrospira sp - Xingkai Che; Ruirui Ding; Qiang Zhang; Yujie Li; Qi Sun; Yuting Li; Zishan Zhang; Wei Wang; Huiyuan Gao (Environmental Science and Pollution Research, 2021)

Mapping daily leaf area index at 30 m resolution over a meadow steppe area by fusing Landsat, Sentinel-2A and MODIS data - Zhenwang Li; Chengquan Huang; Zhiliang Zhu; Feng Gao; Huan Tang; Xiaoping Xin; Lei Ding; Beibei Shen; Jinxun Liu; Baorui Chen; Xu Wang; Ruirui Yan (International Journal of Remote Sensing, 2018)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

MiR-340 Regulates Fibrinolysis and Axon Regrowth Following Sciatic Nerve Injury - Shiying Li; Ruirui Zhang; Ying Yuan; Sheng Yi; Qianqian Chen; Leilei Gong; Jie Liu; Fei Ding; Zheng Cao; Xiaosong Gu (Molecular Neurobiology, 2017)